El llindar neofantàstic en l’obra narrativa de Joan Barceló i Cullerés - Badia-Escolà, Andratx (Studia Romanica Posnaniensia, 2018)
The fantastic is one of the elements in the narrative poetics of Joan Barceló, a seminal Catalan writer of the 70s. The purpose of this article is to analyse the fantastic from a theoretical perspective, including its specific uses in Barceló’s stories and novels, how it works and why. Thus, the paper draws on the concept of the neofantastic to reveal a literary space of aesthetic and ideological transgression that moves among three thresholds: the magical or fairy, the unusual and the absurd or nonsense.